The new longevities. Experience of a group of retired teachers in Berazategui, Argentina - de Antón, Noelia Estela (2023)
In this article, I present the experience of retired teaching workers (teachers, librarians and professors) which took place in Berazategui, Province of Buenos Aires, Argentina, carried out at the time of the COVID-19 pandemic towards the end of the viral contingency. This practice commenced in May 2020 and continues in the present.  In the narration, based on an ethnographic approach, I describe the virtual actions carried out by its members to maintain communication during the viral emergency. Subsequently, once the sanitary measures that promoted social isolation were reduced (and given that most are members of a trade union: CTA de los Trabajadores), I focus on the labor union participation and the face-to-face meetings that took place. These meetings aimed to re-establish interpersonal ties and promote actions within the union list where they participate. Finally, I refer to the weekly virtual meetings held by a small group related to the union environment and named "Jubiladxs y jubilaciones." In addition to the specific topics, they reflect on their life situation and the expectations of continuing with their active, socially productive, and integrated life in their belonging area.